2015
DOI: 10.1634/theoncologist.2015-0180
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal Marginal Zone Lymphoma of Mucosa-Associated Lymphoid Tissue of the Salivary Glands: A Multicenter, International Experience of 248 Patients (IELSG 41)

Abstract: Background. The salivary gland is one of the most common sites involved by nongastric, extranodal marginal zone lymphomas of mucosa‐associated lymphoid tissue (MALT). A large series of patients with long‐term follow‐up has not been documented. This multicenter, international study sought to characterize the clinical characteristics, treatment, and natural history of salivary gland MALT lymphoma. Methods. Patients with biopsy‐confirmed salivary gland MALT lymphoma were identified from multiple international sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 17 publications
0
22
0
10
Order By: Relevance
“…MALT lymphoma usually arises in background of chronic inflammation associated with infective agents, such as H pylori -associated chronic gastritis, [47] or autoimmune diseases, such Sjogren syndrome [48] and Hashimoto thyroiditis. [49] However, the etiology of hepatic malignant lymphomas, especially MALT lymphomas, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MALT lymphoma usually arises in background of chronic inflammation associated with infective agents, such as H pylori -associated chronic gastritis, [47] or autoimmune diseases, such Sjogren syndrome [48] and Hashimoto thyroiditis. [49] However, the etiology of hepatic malignant lymphomas, especially MALT lymphomas, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Ann Arbor staging classification, bilateral lungs and multiple distant skin involvement were classified as stage IV, while bilateral organ involvement in other anatomical sites was defined as stage I disease . Involvement of multiple mucosal sites (MMS) was defined as EMZL in two or more different anatomical organs independent of spleen and BM involvement.…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies lacked statistical power to demonstrate such an association due to a small number of MMS patients at presentation (eg, n = 17 and 24) . Moreover, some studies defined MMS to include bilateral involvement of the same organ, which is usually considered a stage I presentation . Similarly, the incidence and prognostic significance of monoclonal gammopathy (MG) in EMZLs at presentation are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The International External Lymphoma Study Group (IELSG) reported on 247 patients with MALT lymphoma of the salivary glands [12]. In this study, only 5% had primary submandibular gland involvement; in the majority (78%), the parotid gland was involved.…”
Section: Discussionmentioning
confidence: 91%
“…Risk factors associated with salivary gland MALT lymphoma include chronic immune system dysregulation such as Sjögren's syndrome [58] and chronic inflammatory conditions such as sialadenitis [911]. In a large multicenter international study on MALT lymphoma of the salivary gland, 40% of patients had history of autoimmune disease [12]. In the Rare Cancer Network multicenter study [13], 28% of patients had documented history of sialadenitis.…”
Section: Discussionmentioning
confidence: 99%